Bergson and Durational Performance (Re)Ma(r)king Time. - Layton, James (Intellect Books, 2022)
Explores the possibility of an alternative experience of time, one that is closer to the pure duration described by philosopher Henri Bergson. Contributes to contemporary performance analysis, philosophy and Bergson studies and examines aspects of immersive and participatory performance, ritual and online performance. 9 b&w illus.